The Combination of Oral Anticoagulant and Antiplatelet Therapies: Stay One Step Ahead. (September 2020) - Lucà, Fabiana; Giubilato, Simona; Fusco, Stefania Angela Di; Leone, Angelo; Poli, Stefano; Rao, Carmelo Massimiliano; Iorio, Annamaria; Gelsomino, Sandro; Gabrielli, Domenico; Colivicchi, Furio; De Luca, Leonardo; Gulizia, Michele Massimo
Antithrombotic drugs, which include antiplatelets and anticoagulants, are effective in prevention and treatment of many cardiovascular disorders such as acute coronary syndromes, stroke, and venous thromboembolism and are among the drugs most commonly prescribed worldwide. The advent of direct oral anticoagulants, which are safer alternatives to vitamin K antagonists and do not require laboratory monitoring, has revolutionized the treatment of nonvalvular atrial fibrillation and venous thromboembolism. The combination of oral anticoagulant and antiplatelet therapy is required in many conditions of great clinical impact such as the coexistence of atrial fibrillation and coronary artery disease, with indication to percutaneous coronary intervention. However, strategies that combine anticoagulant and antiplatelet therapies lead to a significant increase in bleeding rates and it is crucial to find the right combination in the single patient in order to optimize the ischemic and bleeding risk. The aim of this review is to explore the evidence and controversies regarding the optimal combination of anticoagulant and antiplatelet therapy through the consideration of past dogmas and new perspectives from recent clinical trials and to propose a tailored therapeutic approach, according to specific clinical scenarios and individual patient characteristics. In particular, we separately explored the clinical settings of stable and acute coronary syndromes and percutaneous revascularization in patients with atrial fibrillation.